Tunnel FET ambipolarity‐based energy efficient and robust true random number generator against reverse engineering attacks. Issue 5 (1st July 2019) - Japa, Aditya; Majumder, Manoj Kumar; Sahoo, Subhendu K.; Vaddi, Ramesh
Abstract : This study presents a true random number generator (TRNG) harvesting random bits from delay variations of ambipolarity‐based ring oscillator, designed using 20 nm InAs Tunnel FET (TFET). Exploiting the TFET transmission gate (TG) functional failure, TFET ambipolarity‐based ring oscillator design has been proposed. Random variations are observed in the oscillating frequency of proposed ring oscillator by changing the TFET device ambipolarity. Exploring the same, a TFET ambipolarity‐based TRNG circuit has been demonstrated. XOR gate‐based post‐processing unit is designed to further enhance the unpredictability and randomness of the output bits. The proposed TRNG has passed various NIST tests performed at a supply voltage of 0.5 V. In 20 nm, the proposed TFET TRNG has an area as low as 90 pm 2 and consumes 5.4 pJ/bit at 0.5 V supply voltage. Ambipolarity‐based circuit design makes the proposed TRNG robust against reverse engineering attacks.